Evolutionary Origins of Recurrent Pancreatic Cancer - Sakamoto, Hitomi; Attiyeh, Marc; Gerold, Jeff; Makohon-Moore, Alvin P; Hayashi, Akimasa; Hong, Jungeui; Kappagantula, Rajya; Zhang, Lance; Melchor, Jerry; Reiter, Johannes; Heyde, Alex; Bielski, Craig; et al. (bioRxiv, 2019)
Surgery is the only curative option for Stage I/II pancreatic cancer, nonetheless most patients will recur after surgery and die of their disease. To identify novel opportunities for management of recurrent pancreatic cancer we performed whole exome or targeted sequencing of 10 resected primary cancers and matched intrapancreatic recurrences or distant metastases. We identified that adjuvant or first-line platinum therapy corresponds to an increased mutational burden of recurrent disease. Recurrent disease is enriched for mutations that activate Mapk/Erk and PI3K/AKT signaling and develops from a monophyletic or polyphyletic origin. Treatment induced genetic bottlenecks lead to a modified genetic landscape and subclonal heterogeneity for driver gene alterations in part due to intermetastatic seeding. In one patient what was believed to be recurrent disease was an independent (second) primary tumor. These findings advocate for combination therapies with immunotherapy and routine post-treatment sampling as a component of management of recurrent pancreatic cancer.